Emergence of microfluidics for next generation biomedical devices - Preetam, Subham; Nahak, Bishal Kumar; Patra, Santanu; Toncu, Dana Cristina; Park, Sukho; Syväjärvi, Mikael; Orive, Gorka; Tiwari, Ashutosh (Biosensors and bioelectronics. X, 2022)
The attention in lab-on-a-chip devices with their potent application in medical engineering has prolonged swiftly over the last ten years. Travelling through the technology development, innovative microfluidics devices shown enormous potential to lift the lab-on-a-chip biomedical research in traditions that are not imaginable using conventional techniques. The advances in the arena of microfluidics have prompted high-tech uprisings in numerous biomedical disciplines, including diagnostics, single-cell analysis, micro- and nano device fabrication, organ-in-chip platforms, and med-tech applications. The speedy development is motivated by the cumulative cooperation among central nanomaterials advances and innovative microfluidic aptitudes in the range of biomedical applications. Microfluidic gadgets presently undertake a significant part in numerous organic, synthetic, and designing applications, that have multiple approaches to create the vital channel and highlight measurements. In this review, the critical assessments on the frontiers of microfluidic platforms are carried out towards advancements in the microfluidic capabilities for the new-edge biomedical applications. It has been exhibited that microfluidics offers a scope of benefits contrasted with customary strategies, including further developed controllability and consistency specified by nanomaterial attributes. Herein, authors have discussed how innumerable nanomaterials empower the manufacture of microfluidic systems with advanced optical, mechanical, electrical chemical, and bio-interfacial properties ranging from the basics of microfluidics, various factors, types, and fabrication procedure to biomedical applications. A comprehensive investigation in the state-of-the-art usage of microfluidics in biomedical field is steered exemplarily to understand the significant advantages. Moreover, our assessment provides an interdisciplinary overview of modern microfabrication strategies that can be adopted for academic and industrial interests. •Herein, the frontiers of microfluidic platforms have been summarized.•Various applications of microfluidic in biomedical engineering has been discussed.•Assessed the role of nanomaterials to empower the manufacture of microfluidics.•Utility of microfabrication strategies for industrial purposes has been discussed.•Strategies to bridging gap between microfluidics and end-user has been summarized.